Pendampingan Identifikasi Kecacatan Kualitas Produk Melalui Review Pelanggan di E-commerce - Anik Nur Habyba; Iveline Anne Marie; Rahmi Maulidya; Indah Permata Sari; Triwulandari Satitidjati Dewayana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
E-commerce has been proven to be able to increase product sales. PT TIJ utilized e-commerce well and increased women's bag product sales. During 2023, PT TIJ will be able to triple bag production and online sales through several e-commerce sites. Various problems are also encountered as production capacity increases, especially regarding returned customer products. Customers receive products with product defects in bags purchased via e-commerce. This defect can occur due to the shipping or production processes. Customer review data contains many product defect data that PT TIJ has not analyzed. This data is widely accessible to competitors. This community service assists in identifying product defects through customer review data in e-commerce. Apart from that, how should communication between departments be carried out? The mentoring participants comprised 14 employees and represented each of the Production, Quality Control, and Marketing departments. The findings of PT TIJ's customer review analysis can identify product defects in ratings 1-3 with the most reviews. Apart from that, Shopee e-commerce is the main priority for defect identification data because it has the highest number of product assessments compared to other platforms. After the mentoring was carried out, there was an increase in participants' understanding of product quality management. However, in the future, the program needs to be carried out more intensively and adapted to the participant's job description.